Antimicrobial properties and applications of metal nanoparticles biosynthesized by green methods - Maťátková, Olga; Michailidu, Jana; Miškovská, Anna; Kolouchová, Irena; Masák, Jan; Čejková, Alena (Biotechnology advances, 2022)
There is a growing interest in the potential and application of metal nanoparticles across many fields. A vast array of techniques for metal nanoparticle synthesis has been discovered; however, sustainability, cost-effectiveness, and environmental concerns favor the green biological approach, using various plant and microbial sources. This review describes the diversity in green methods for nanoparticle biosynthesis, antimicrobial properties of metal nanoparticles and their potential applications. Metal nanoparticle biosynthesis by extracts and solutions obtained from plants, bacteria, fungi and templates such as viruses are discussed. As biosynthesized nanoparticles have been proven to possess antibacterial, antifungal, and even antiviral properties, these are discussed in detail, with silver and gold nanoparticles as the most studied and with the highest potential for medical application. The focus on prospective antimicrobial applications of nanoparticles stems from the arising resistance of many serious pathogens to traditional disinfectants and antibiotics. Other fields for the application of biosynthesized nanoparticles are also stated briefly, such as in agriculture as pesticides, in wastewater treatment and bioremediation. Finally, the limitations and safety issues connected with widespread use of nanoparticles are discussed.
Keywords: Antimicrobial properties; rostliny; Nanoparticles application; Anti-Bacterial Agents; antiinfekční látky; Metal nanoparticles biosynthesis; Anti-Infective Agents; Prospective Studies; rostlinné extrakty; Plants; Green Chemistry Technology; prospektivní studie; zlato; Green methods; antibakteriální látky; Gold; Plant Extracts; Limitations and safety; Metal Nanoparticles; kovové nanočástice; technologie zelené chemie